Large-aperture adaptive optical system for correcting wavefront distortions of a petawatt Ti : sapphire laser beam. (February 2022) - Samarkin, V V; Alexandrov, A G; Galaktionov, I V; Kudryashov, A V; Nikitin, A N; Rukosuev, A L; Toporovsky, V V; Sheldakova, Yu V
Abstract: This paper reports a large-aperture adaptive optical system with a bimorph deformable mirror and Shack?Hartmann wavefront sensor for aberration correction and beam focusing improvement in state-of-the-art petawatt Ti : sapphire lasers. We consider methods for providing feedback to the wavefront sensor and obtaining an objective wavefront that optimises beam focusing onto a target. The use of an adaptive system with a controlled 127-channel 320-mm-aperture mirror in a Ti : sapphire laser with an output power of 4.2 PW has made it possible to obtain a record high laser beam intensity: 1.1 × 10 23 W cm -2 .